LAYANAN PEMBERDAYAAN PEREMPUAN DAN ANAK PADA PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK “CITRA TEPIAN” KOTA SAMARINDA - Oktovianus Kondorura; Sutadji Sutadji; Fajar Apriani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
The research objectives were to determine the type of service, analyze and identify supporting factors and inhibiting factors for empowerment services for women and children in Samarinda City. With this type of qualitative research. Data collection techniques are observation, interviews and documentation. Then the interactive model data analysis technique. The results of research on empowerment services for women and children at the Integrated Service Center for Empowerment of Women and Children